Brand Reputation, Brand Awareness Dan Brand Image Terhadap Kepercayaan Dan Loyalitas Donatur - Cahyadi, Nur; Respati, Putra Panji (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2024)
Background – The increasing variety of Amil Zakat, Infaq and Sadaqah Institutions (LAZIS) in Indonesia has an impact on the level of competition that is so tight and competitive, therefore the institution immediately determines what strategies are considered effective and attractive to new or their old donors.Aim – This study aims to determine the interaction between brand reputation, brand awareness and brand image on trust and loyalty.Design/ methodology/ approach – Data collection was carried out using a questionnaire to LAZIS XYZ donors in Gresik and the technique used was convenience sampling and up to 197 respondents. In this study, the analysis tool used was Partial Least Square (PLS). Findings – The results of this study: (1) There is a significant interaction between brand reputation (BR) variables on trust (K). (2) There is a significant interaction between brand awareness (BA) variables on trust (K). (3) There is a significant interaction between the brand image (BI) variable and trust (K). (4) There is a significant interaction between the trust variable (K) and loyalty (L).Research implication – This research can provide an overview of brand strategies that can increase trust and loyalty in donors of Lembaga Amil, Zakat, dan Infaq (LAZIS). Limitations – The limitation of this study is that the donor trust variable can only be explained by 70.4% by the brand reputation, brand awareness and brand image variables, while 29.6% is explained by other variables outside the model. The donor loyalty variable can only be explained by the trust variable by 74.4%, for the remaining 25.6% explained by other variables outside the model.